A novel H2O2photoelectrochemical sensor based on ternary RGO/Ag-TiO2 nanotube arrays nanocomposite. (1st April 2021) - Li, Li; Zhai, Liying; Liu, Huan; Li, Boya; Li, Mingqing; Wang, Baohui
Abstract: Ternary nanocomposite photoelectrodes composed of Ag nanoparticles, reduced graphene oxide (RGO), and TiO2 nanotube arrays (TNTs) were successfully designed and achieved by a combining technique of cyclic voltammetry and anodic oxidation. Herein, the obtained RGO/Ag-TNTs composites were employed for photoelectrochemical (PEC) monitoring platform of hydrogen peroxide (H2 O2 ) for the first time. Compared to pure TNTs, Ag-TNTs, and RGO-TNTs, the ternary RGO/Ag-TNTs nanocomposites with appropriate loading amount of RGO and Ag show much higher PEC activity, which were contributed to the synergistic effect resulting from the effective incorporation of Ag nanoparticles and RGO onto the TNTs to accelerate the electron transfer, increase the charge carrier density and prolong the electron lifetime demonstrated by electrochemical impedance spectroscopy (EIS), Mott-Schottky (M-S) measurements and open circuit voltage decay (OCVD) measurement. Under the optimal experimental conditions, the as-prepared PEC sensors exhibited an extremely wide dynamic range from 10 −7  nM to 10 mM, and in the range of 0.1–10 mM with higher sensitivity and a detection limit of 20 μM. Moreover, the PEC sensors displayed good reproducibility, long-term stability, and selectivity toward the determination of H2 O2 . These excellent results make the as-developed ternary RGO/Ag-TNTs nanocomposites a promising candidate in PEC detection H2 O2 .